DIGITAL INDIA INITIATIVES - Shukla, Rajesh Kumar; Singh, Amar Pal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This article proposes efforts that the Government of India has initiated towards digitizing India and working towards a digitally empowered society and economy. This initiative is directed at making electronic services from the governments available to citizens and strengthening digital infrastructure. It also explains which are the key initiatives taken by Government of India to bridge the digital divide.